+0  
 
0
276
3
avatar

if sqrt(2)*sqrt(8) = sqrt(2*8) why isnt sqrt(-1)*sqrt(-1)=sqrt(-1*-1)

Guest Apr 24, 2017
 #1
avatar+92781 
+1

 

if sqrt(2)*sqrt(8) = sqrt(2*8) why isnt sqrt(-1)*sqrt(-1)=sqrt(-1*-1)

 

\(if\;\; \sqrt2*\sqrt8= \sqrt{2*8}\\\text{ why isn't }\quad\\ \sqrt{-1}*\sqrt{-1}=\sqrt{-1*-1}\)

 

 

The rules for real numbers often do not extend to imaginary numbers. 

This is one such case.

 

Alan, or someone else might be able to give a better explanation.   :/

Melody  Apr 24, 2017
 #2
avatar
0

sqrt((-1)*(-1)) = +/-1

Guest Apr 24, 2017
 #3
avatar+87301 
+1

The rule is

 

√a  *  √b   =   √ [ a * b]   only if a, b  ≥  0

 

 

 

cool cool cool

CPhill  Apr 24, 2017

11 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.